2004
DOI: 10.1016/j.chembiol.2004.03.011
|View full text |Cite
|
Sign up to set email alerts
|

Generation of New Landomycins by Combinatorial Biosynthetic Manipulation of the LndGT4 Gene of the Landomycin E Cluster in S. globisporus

Abstract: A 3 kb DNA fragment from the Streptomyces globisporus 1912 landomycin E (LaE) biosynthetic gene cluster (lnd) was completely sequenced. Three open reading frames were identified, lndGT4, lndZ4, and lndZ5, whose probable translation products resemble a glycosyltransferase, a reductase, and a hydroxylase, respectively. Studies of generated mutants from disruption and complementation experiments involving the lndGT4 gene allowed us to determine that LndGT4 controls the terminal L-rhodinose sugar attachment during… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
83
0
6

Year Published

2004
2004
2008
2008

Publication Types

Select...
6
1

Relationship

6
1

Authors

Journals

citations
Cited by 65 publications
(89 citation statements)
references
References 29 publications
0
83
0
6
Order By: Relevance
“…The disappearance of the fed metabolites 5 and 9 as well as the appearance of landomycin E (1) was monitored by HPLC-MS; a peak not observable in a control experiment (in which no compound was added) after feeding with tetrangomycin or rabelomycin was identified to be landomycin E according to its HPLC relative retention time and its UV and MS spectra. 12 No such transformation was detected in the corresponding cultures after feeding with the same amount of the other three compounds. Accordingly, it was concluded that tetrangomycin (5) and rabelomycin (9) are intermediates in the biosynthesis of landomycin E, while the other three metabolites (compounds 6-8) yielded by S. globisporus M12 strain are shunt products.…”
Section: Feeding Experimentsmentioning
confidence: 94%
See 3 more Smart Citations
“…The disappearance of the fed metabolites 5 and 9 as well as the appearance of landomycin E (1) was monitored by HPLC-MS; a peak not observable in a control experiment (in which no compound was added) after feeding with tetrangomycin or rabelomycin was identified to be landomycin E according to its HPLC relative retention time and its UV and MS spectra. 12 No such transformation was detected in the corresponding cultures after feeding with the same amount of the other three compounds. Accordingly, it was concluded that tetrangomycin (5) and rabelomycin (9) are intermediates in the biosynthesis of landomycin E, while the other three metabolites (compounds 6-8) yielded by S. globisporus M12 strain are shunt products.…”
Section: Feeding Experimentsmentioning
confidence: 94%
“…Whereas the formation of tetrangulol (8) is most likely due to a spontaneous dehydration and aromatization of ring A of 5 22,23 and the formation of shunt product 6 can be explained by a certain flexibility of the enzymes LndZ4/Z5, which are responsible for the 11-hydroxylation, 12 the formation of angucyclinone 7 cannot readily be explained, because a 4-hydroxylation has never been observed before in any of the landomycins, neither from S. globisporus nor from S. cyanogenus. Nevertheless, this shunt pathway toward 7 might be caused by one of the two remaining oxygenases of the lnd gene cluster, e.g., LndE, or more likely by an oxygenase of S. globisporus, which is not part of the lnd pathway.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The highest homologies were found with LanGT2 (38% amino-acid identity), a GT presumed to be involved in attaching the first D-olivose to landomycin aglycon, [13][14][15] and UrdGT2 (31% amino-acid identity), which is the C-GT of the urdamycin biosynthetic pathway. [16][17][18] The previously reported putative GilGT protein had 495 amino acids, which is approximately 120 amino acids longer than any other polyketide GT found so far.…”
Section: Sequence Analysismentioning
confidence: 99%